'The Chemical Worker', 1948 (1948)
1948 1945-1960 "'The Chemical Worker', 1948" [HFR0083], 1948 This cartoon from the cover of the Chemical Workers Union magazine supports the public ownership or nationalisation of the industry and links the major chemical companies with warmongering and the development of the atomic bomb.